Method for synthesizing ZSM-48 molecular sieve with low silica-alumina ratio in double-alkali-source system and application of ZSM-48 molecular sieve

By using pyrrolidine as a template agent in a dual alkali source system, the problem of difficulty in synthesizing ZSM-48 molecular sieve in the prior art is solved, and efficient, fast and low-cost synthesis is achieved. The product is suitable for hydrogen isomerization reactions.

CN119797390AActive Publication Date: 2025-04-11DALIAN UNIV OF TECH
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510004571.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-04-11
Estimated Expiration
2045-01-02

AI Technical Summary

Technical Problem

The prior art is difficult to efficiently and quickly synthesize ZSM-48 molecular sieves with high crystallinity and low silicon-aluminum ratio, and the commonly used template agents are costly and complex in structure, making it difficult to produce on a large scale.

Method used

The ZSM-48 molecular sieve is synthesized in a dual alkali source system using simple structure and low cost pyrrolidine as a template agent. By regulating the ratio of NaOH and KOH and the specific material addition order, it ensures the full dissociation of silicon species and the effective entry of aluminum species into the molecular sieve skeleton.

Benefits of technology

It has achieved efficient and rapid synthesis of low silicon-aluminum ratio ZSM-48 molecular sieve with a silicon-aluminum ratio of 20-100. The product has high crystallinity, regular morphology, high acid density and acid strength, and is suitable for hydrogen isomerization reactions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119797390A_ABST
    Figure CN119797390A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of synthesis of molecular sieves, and discloses a method for synthesizing a ZSM-48 molecular sieve with a low silica-alumina ratio in a double-alkali-source system and application, pyrrolidine is used as a template agent, sodium hydroxide and potassium hydroxide are used as double alkali sources, and the method comprises the following steps: uniformly mixing an alkali source, a silicon source and deionized water at 40-80 DEG C to obtain a mixture A; uniformly mixing an aluminum source, a template agent and deionized water, and slowly adding the mixture into the mixture A to obtain an initial gel mixed solution; carrying out hydrothermal crystallization treatment on the initial gel, and then filtering, washing, drying and roasting to obtain the ZSM-48 molecular sieve. The ZSM-48 molecular sieve synthesized by the method provided by the invention is regular in morphology, uniform in particle and highly crystalline, the silicon-aluminum ratio is 20-100 according to the calculation range of SiO2 / Al2O3, and the ZSM-48 molecular sieve has higher isohexadecane selectivity and yield when being applied to normal hexadecane hydroisomerization reaction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of molecular sieve synthesis, and relates to a synthesis method of a low silicon-aluminum ratio ZSM-48 molecular sieve and its application in a hydrogen isomerization reaction. Background Art

[0002] ZSM-48 molecular sieve is a high-silicon zeolite, which was first discovered by Schlenker et al. (Nature, 1981, 294: 340-342) when synthesizing ZSM-39 high-silicon molecular sieve. Its morphology is fibrous rod-shaped crystals. The pore structure of ZSM-48 molecular sieve is a one-dimensional linear pore with a ten-membered ring opening, which belongs to the *MRE topological structure and has a pore size of 0.56×0.56nm. Therefore, ZSM-48 molecular sieve has a molecular shape-selective effect of a specific size, and its grains grow along the one-dimensional straight channel direction and appear as needle-shaped grains or nano-needle-shaped crystals aggregated into nano-rods, which is an ideal carrier for the hydroisomerization of straight-chain alkanes. Hydroisomerization of straight-chain alkanes is an important oil processing technology. It plays an important role in the high-value conversion of long-chain alkanes derived from clean energy such as biomass oil, Fischer-Tropsch synthesis oil and waste plastic pyrolysis oil. It is widely used in the quality improvement process of high-end essential oils such as sustainable aviation fuel and lubricant base oil. Therefore, the rapid synthesis of ZSM-48 molecular sieves with high crystallinity, low silicon-aluminum ratio and high acid density is of great significance for the dual carbon target.

[0003] At present, the commonly used templates for synthesizing ZSM-48 molecular sieves can be divided into: (1) linear organic alkylamines synergistic with tetramethylammonium ions (US4397827, US4448675), (2) linear organic diamines (US8003074B2, US4423021, US5961951), (3) diquaternary ammonium salt ions (US6923949B1, US7482300B2, US7625478B2, US9433935B2), (4) new bifunctional surfactants (CN103803576A, CN104003413B, Chem. Mater., 2018, 30: 1839-1843), etc.

[0004] In the early 1980s, Mobil Corporation first disclosed a patent for synthesizing ZSM-48 molecular sieves using linear organic alkylamines (C2-C12 alkylamines, preferably C3-C5 alkylamines) in conjunction with tetramethylammonium hydroxide as a template (US4397827). Subsequently, the company synthesized ZSM-48 molecular sieves using single or double molecule N-methylpyridine as a template (US4585747), but the initial gel silicon-aluminum ratio was required to be greater than 250 and the crystallization time was greater than 5 days. The synthesis of low silicon-aluminum ratio ZSM-48 molecular sieves has always been the target of continuous research by researchers. US5961951 discloses a method for synthesizing ZSM-48 molecular sieves using ethylenediamine as a template, in which the initial gel silicon-aluminum feed ratio can be reduced to 200 and the crystallization cycle is shortened to less than 3 days.

[0005] As a zeolite derived from a high-silica gel system, ZSM-48 molecular sieve is often obtained from an initial gel with a high feed silicon-aluminum ratio (SiO2 / Al2O3>150) and a low alkalinity (Na2O / SiO2=0.02-0.08). Although the silicon-aluminum ratio of the molecular sieve can be reduced to a certain extent by reducing the feed silicon-aluminum ratio, it is difficult to obtain ZSM-48 within a lower silicon-aluminum ratio range (SiO2 / Al2O3<100). Low silicon-aluminum ratio zeolites such as FAU, SOD, and LTA usually need to be crystallized from an initial gel with a higher alkalinity. This is because a high concentration of OH- preferentially dissolves silicon species, allowing aluminum species to enter the molecular sieve framework. However, the crystallization of ZSM-48 molecular sieve requires a low alkalinity of the gel system, which is contradictory to the crystallization of low silicon-aluminum ratio zeolites, which requires a high alkalinity gel system. It has been reported that pyrrolidine can be used as a template for the synthesis of ZSM-48 molecular sieve (Zeolites, 1991, 11: 573-576; Journal of Catalysis, 1999, 185: 435-444). These two reports first used a high concentration of alkaline solution to fully dissociate the silicon source (Na2O / SiO2 = 0.19), and then mixed it with an aqueous solution containing concentrated sulfuric acid and an aluminum source. The excess OH- was neutralized by concentrated sulfuric acid to meet the low alkalinity required for the crystallization of the ZSM-48 molecular sieve. However, the silicon-to-aluminum ratio of the synthesized ZSM-48 molecular sieve was still greater than 150. Similarly, the synthesis of ZSM-48 molecular sieve containing heteroatom Sn using pyrrolidine as template also adopted a similar idea (Studies in Surface Science and Catalysis, 1997, 105: 357-364): firstly, a high concentration of alkaline solution was used to dissociate the silicon source, and then concentrated sulfuric acid was used to reduce the alkalinity of the gel system to meet the alkalinity range required for the crystallization of ZSM-48 molecular sieve.

[0006] After 2005, Mobil Corporation successively disclosed patents (US6923949B1, US7482300B2, US7625478B2, US9433935B2) for synthesizing ZSM-48 molecular sieves with a silicon-aluminum ratio as low as 100 using hexamethylammonium chloride as a template. The crystallization time can be shortened to 2 days, but the cost of the template is relatively high. Domestic patents also use a variety of different templates to synthesize low silicon-aluminum ratio ZSM-48 molecular sieves, such as allyltrimethylammonium chloride (CN110127719B), 12-crown ether-4 (CN103803576A), N,N-diethylhexamethyleneimine quaternary ammonium base (CN102040231B), diazoxane dibromide (CN106608635B), 1,n-bis(N-methylpyrrolidine)hexane bromide (n=1-10) (CN104003413B) and organic mixed templates (dibromohexane, trimethylamine and ethanol) (CN102910642B), etc.

[0007] In summary, simple-structured, low-cost organic amines (n-octylamine in combination with tetramethylammonium bromide, 1,6-hexanediamine, pyrrolidine, etc.) are often used to synthesize ZSM-48 molecular sieves with a silicon-aluminum ratio higher than 150. However, due to the low acid density and acid strength of the product, the application of ZSM-48 molecular sieves in acid-catalyzed reactions is severely limited. Since the discovery of ZSM-48 molecular sieves, although molecular sieve synthesis technology has continued to advance, and certain progress has been made in synthesizing ZSM-48 molecular sieves with a silicon-aluminum ratio lower than 150, it is often necessary to use expensive and complex template agents, making it difficult to mass-produce ZSM-48 molecular sieves. Therefore, how to use new, simple, and inexpensive template agents to efficiently and quickly synthesize high-crystallinity, low-silicon-aluminum ratio ZSM-48 molecular sieves remains a current research hotspot and difficulty. Summary of the invention

[0008] The present invention selects an organic amine with a simple structure and relatively low cost as a template agent, and provides a method for synthesizing a high-crystallinity, low-silicon-aluminum ratio ZSM-48 molecular sieve in a dual-alkali source system. By regulating two strong bases, NaOH and KOH, to form a dual-alkali source according to a specific ratio, under the condition of a stirring temperature of 40-80°C, the silicon source is first dissolved by the mineralization of OH-, and the silicon species are fully dissociated, so that the aluminum species can more easily enter the framework of the ZSM-48 molecular sieve. The method can efficiently and quickly synthesize a low-silicon-aluminum ratio ZSM-48 molecular sieve (SiO2 / Al2O3, 20-100), and at the same time, the molecular sieve is used as a carrier to prepare a catalyst for the hydroisomerization reaction of linear alkanes.

[0009] One of the purposes of the present invention is to provide a gel composition system different from the existing synthetic ZSM-48 molecular sieve; the second purpose of the present invention is to provide an efficient and low-cost method for synthesizing ZSM-48 molecular sieve; the third purpose of the present invention is to provide a method for synthesizing ZSM-48 molecular sieve with a specific morphology and a low silicon-aluminum ratio.

[0010] The technical solution of the present invention:

[0011] A method for synthesizing a low silicon-aluminum ratio ZSM-48 molecular sieve in a dual alkali source system, the steps are as follows:

[0012] (1) First, a mixture of an alkali source, a silicon source and deionized water is placed at 40-80° C. and vigorously stirred to obtain a mixture A;

[0013] (2) mixing the aluminum source, template and deionized water uniformly, slowly adding the mixture A in step (1), and stirring thoroughly to obtain an initial gel mixture;

[0014] (3) transferring the initial gel mixture into a crystallization kettle for hydrothermal crystallization at a crystallization temperature of 130-210° C. for a crystallization time of 12-72 h; either static crystallization or dynamic crystallization;

[0015] (4) The solid product obtained by the hydrothermal crystallization treatment is filtered, washed, dried and calcined to obtain a ZSM-48 molecular sieve.

[0016] In the present invention, pyrrolidine is used as a template, sodium hydroxide and potassium hydroxide are used as a dual alkali source, and according to the specific addition order described in steps (1) and (2), a silicon source, an aluminum source, a template, an alkali source and deionized water are added in a molar ratio of 1: (0.01-0.05): (0.05-1.2): (0.02-0.12): (18-50) to prepare an initial gel, and the mixture is fully stirred and mixed for 2-6 hours, preferably 3-4 hours, and then transferred into a crystallization kettle, and the temperature is rapidly raised to a crystallization temperature of 130-210° C., preferably 155-195° C., and the crystallization time is 12-72 hours, preferably 24-48 hours, and static crystallization or dynamic crystallization with a rotation speed of 20-1000RPM is performed. The molar ratio of the initial gel mixture is preferably 1: (0.01-0.05): (0.2-0.8): (0.03-0.08): (25-40).

[0017] In the present invention, the pH range of the initial gel is controlled to be 12.3-13.8, preferably 12.6-13.4, wherein the silicon source, aluminum source and alkali source in steps (1) and (2) are calculated as SiO2, Al2O3 and Me2O, respectively. The specific order of addition is as follows: the mixed solution prepared by the aluminum source, template and deionized water in step (2) is slowly added to the mixture A prepared by the alkali source, silicon source and deionized water in step (1). The mixing and stirring time of the alkali source, silicon source and deionized water in step (1) is 0.5-4h, preferably 2-3h, and the stirring temperature is 40-80°C; the mixing and stirring time of the aluminum source, template and deionized water in step (2) is 0.1-1h, preferably 0.25-0.5h, and the stirring is carried out at room temperature.

[0018] In the present invention, the template is pyrrolidine. The aluminum source is one or a mixture of two or more of aluminum nitrate, aluminum sulfate, sodium metaaluminate, and aluminum isopropoxide, preferably aluminum nitrate and aluminum sulfate. The silicon source is one or a mixture of two or more of fumed silica, silica sol, tetraethyl orthosilicate, and water glass, preferably fumed silica and silica sol.

[0019] The alkali source is a mixture of sodium hydroxide and potassium hydroxide, and the molar ratio of the two alkali sources is Na2O:K2O=0.2-8.0.

[0020] In the present invention, the molecular sieve solid product obtained by hydrothermal crystallization treatment is filtered, washed, dried and calcined to obtain a low silicon-aluminum ratio ZSM-48 molecular sieve, and the silicon-aluminum ratio (SiO2 / Al2O3) ranges from 20 to 100.

[0021] In the present invention, the processes of hydrothermal crystallization, filtration, washing, drying and calcination are all technical means and technical conditions commonly used in the synthesis of molecular sieves.

[0022] In the present invention, the morphology of the low silicon-aluminum ratio ZSM-48 molecular sieve is a spindle shape formed by aggregation of nano needles, and the silicon-aluminum ratio ranges from 20 to 100. The morphology of the synthesized ZSM-48 molecular sieve.

[0023] In the present invention, the template is pyrrolidine, and the double alkali source is sodium hydroxide and potassium hydroxide, which are different from the existing gel composition system for synthesizing ZSM-48 molecular sieves; the synthesis method of the ZSM-48 molecular sieve is efficient and fast, the product has high crystallinity, and the template structure is simple and the cost is relatively low. The ZSM-48 molecular sieve synthesized according to the method has a specific crystal morphology, which is specifically manifested as spindle-shaped grains formed by the aggregation of nano needles. The ZSM-48 molecular sieve synthesized according to the method has a low silicon-aluminum ratio and a high acid density, and the silicon-aluminum ratio ranges from 20 to 100.

[0024] In the present invention, the ZSM-48 molecular sieve obtained according to the synthesis method is used as a carrier, and the catalyst prepared by loading the metal by the impregnation method is applied to the hydroisomerization reaction, and a higher isomerization product yield can be obtained. The metal is one or a mixture of two or more of Pt, Pd, Ni, and Mo.

[0025] In previous reports, when ZSM-48 molecular sieves were synthesized using simple organic amines as templates, the initial gel's silicon-aluminum ratio was usually higher than 200, and during the hydrothermal reaction, due to the competitive growth of structural units such as cristobalite, impurity crystals were easily generated. The nucleation and crystallization of ZSM-48 molecular sieves require low alkalinity conditions, but the crystallization of low silicon-aluminum ratio zeolite molecular sieves requires higher alkalinity. Therefore, the efficient synthesis of ZSM-48 and the requirement for a low silicon-aluminum ratio of the molecular sieve are contradictory. How to synthesize ZSM-48 molecular sieves in low-alkalinity initial gels while ensuring that aluminum species enter the molecular sieve framework is the key and difficulty in synthesizing low silicon-aluminum ratio ZSM-48 molecular sieves. Although there have been reports that a high-concentration alkali solution was used to dissociate the silicon source and then concentrated sulfuric acid was used to reduce the alkalinity of the gel system to promote the dissociation of the silicon source and the entry of aluminum species into the molecular sieve framework, the silicon-aluminum ratio of the synthesized ZSM-48 molecular sieve is still greater than 150.

[0026] According to a large number of experimental basic studies, the present invention finds that the premise for aluminum species to enter the molecular sieve framework is that the silicon species in the initial gel need to be fully dissociated under the action of the alkali source. Therefore, the present invention uses pyrrolidine with simple structure and low cost as a template agent, and synthesizes a low silicon-aluminum ratio, regular morphology, uniform particles, and highly crystalline ZSM-48 molecular sieve by selecting a suitable double alkali source, controlling the material mixing order, and reasonably adjusting the molar ratio of each material in the gel system. Sodium hydroxide or potassium hydroxide is not enough as a single alkali source to fully mineralize and dissociate silicon species. The present invention selects sodium hydroxide and potassium hydroxide to form a double alkali source in a specific molar ratio. Under the condition of a stirring temperature of 40-80°C, the double alkali source is first used to fully dissociate the silicon species, and then an aqueous solution composed of an aluminum source and a template agent is added, so that the aluminum species can more effectively enter between the silicon species to form an aluminum-rich molecular sieve framework, thereby efficiently synthesizing a low silicon-aluminum ratio ZSM-48 molecular sieve. Since the metallic property of potassium is slightly stronger than that of sodium, potassium hydroxide is more likely to ionize hydroxide ions (OH-) in aqueous solution. Potassium hydroxide and sodium hydroxide can be used together as alkaline sources to increase the degree of dissociation of OH- from silicon sources. Since the nucleation and crystallization of ZSM-48 molecular sieves require high alkalinity accuracy and the degree of dissociation of silicon sources, the slight difference between the dual alkaline source of potassium hydroxide and sodium hydroxide and the single alkaline source is crucial to the efficient synthesis of low silicon-aluminum ratio ZSM-48 molecular sieves.

[0027] The method of the present invention requires a specific order of adding materials: first, a double alkali source is used to dissociate silicon species, and then an aqueous solution composed of an aluminum source and a template agent is added. This specific order of adding materials is to ensure that the double alkali source fully dissolves and dissociates the silicon source, so that the aluminum species can be effectively introduced into the silicon source fragment and then into the molecular sieve framework. The method of the present invention uses a double alkali source to directly dissociate silicon species, and the alkalinity (Na2O / SiO2) is preferably in the range of only 0.03-0.08, which can avoid the use of excessive alkali, and there is no need to add concentrated sulfuric acid to adjust the pH value of the initial gel, which can effectively reduce the amount of concentrated alkali and concentrated acid.

[0028] In summary, the method of the present invention adopts dual alkali sources to preferentially dissociate silicon species, which can not only ensure the low alkalinity requirement of the ZSM-48 nucleation and crystallization process, but also effectively promote the entry of aluminum species into the silicon fragments, and achieve the goal of synthesizing a low silicon-aluminum ratio ZSM-48 molecular sieve from an aluminum-rich and low-alkalinity initial gel.

[0029] The ZSM-48 molecular sieve synthesis technology scheme described in the present invention has the following advantages:

[0030] 1. The ZSM-48 molecular sieve synthesized by the present invention has regular morphology, uniform particles, high crystallinity, a silicon-aluminum ratio (SiO2 / Al2O3) range of 20-100, and adjustable acidity. The synthesized ZSM-48 molecular sieve has strong acid properties, high acid density and acid strength, and can be used for reactions such as hydroisomerization in which acid catalysis is the rate-controlling step.

[0031] 2. The present invention uses sodium hydroxide and potassium hydroxide as double alkali sources and pyrrolidine as a template agent. Different from the existing gel composition system for synthesizing ZSM-48 molecular sieves, pyrrolidine has low cost and low dosage, which can greatly save raw material costs; the gel system has a low H2O / SiO2 molar ratio and a high single-pot yield, which is convenient for separating and recovering molecular sieve solid products, and can significantly reduce the synthesis cost. At the same time, it greatly reduces wastewater discharge and environmental pollution caused by the roasting process of organic template agents.

[0032] 3. The ZSM-48 molecular sieve synthesis method of the present invention is simple to operate, does not require multi-step crystallization, does not require the addition of seed crystals, and does not require the addition of concentrated sulfuric acid to adjust the pH. Only by selecting a suitable alkali source, controlling the material mixing sequence, and reasonably adjusting the molar ratio of each material in the gel system, a low silicon-aluminum ratio ZSM-48 molecular sieve can be synthesized. The crystallization cycle is short, the process is simple, and the operating cost is low. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is the XRD diffraction spectrum of ZSM-48 synthesized in Example 1.

[0034] Figure 2 This is the SEM scanning electron microscope image of ZSM-48 synthesized in Example 1.

[0035] Figure 3 This is the XRD diffraction spectrum of ZSM-48 synthesized in Example 2.

[0036] Figure 4 This is the SEM scanning electron microscope image of ZSM-48 synthesized in Example 2.

[0037] Figure 5 This is the XRD diffraction spectrum of ZSM-48 synthesized in Example 3.

[0038] Figure 6 This is the SEM scanning electron microscope image of ZSM-48 synthesized in Example 3.

[0039] Figure 7 This is the XRD diffraction spectrum of the sample synthesized in Example 4.

[0040] Figure 8 This is the XRD diffraction spectrum of the sample synthesized in Example 5.

[0041] Fig. 9 This is the XRD diffraction spectrum of the sample synthesized in Example 6.

[0042] Fig.10 This is the XRD diffraction spectrum of ZSM-48 synthesized in Comparative Example 1.

[0043] Fig.11 The figure is a graph showing the variation trend of the n-hexadecane conversion rate of the catalyst prepared in Example 1 with the reaction temperature.

[0044] Fig.12 This is a graph showing the variation trend of the isohexadecane selectivity of the catalyst prepared in Example 1 with the normal-hexadecane conversion rate.

[0045] Fig.13 The isohexadecane yield of the catalyst prepared in Example 1 varies with the reaction temperature. DETAILED DESCRIPTION

[0046] The present invention will be described in detail below by way of examples, but the present invention is not limited to these examples.

[0047] Example 1

[0048] According to the molar ratio of silicon source, aluminum source, pyrrolidine, alkali source and deionized water of 1:0.01:0.35:0.05:30, wherein the alkali source is a mixture of sodium hydroxide and potassium hydroxide, and the Na / K molar ratio is 0.7, 4.00g aluminum sulfate 18hydrate, 120g silica sol (30wt.%), 0.99g NaOH, 1.98g KOH, 14.94g pyrrolidine and 240g deionized water are weighed respectively. First, the deionized water is divided into two parts, one part is used to dissolve the alkali source and silica sol, and stirred for 1h; then the aluminum source and pyrrolidine are dissolved in the other part of deionized water, stirred for 0.25h, and slowly added to the mixed solution of the alkali source and silica sol to obtain the initial gel mixed solution. After continuous vigorous stirring for 3h, it is transferred to a 500ml crystallization kettle, and the temperature is quickly raised to 180℃, and static crystallization is carried out for 2 days. The solid product was filtered and washed, and the filter cake was placed in an oven at 100°C for 12 hours and then calcined at 550°C for 6 hours to obtain a ZSM-48 molecular sieve. According to ICP test analysis, the silicon-aluminum ratio of the obtained ZSM-48 molecular sieve was 91.

[0049] Example 2

[0050] The steps in Example 1 were repeated, except that the molar ratio of silicon source, aluminum source, pyrrolidine, alkali source and deionized water was 1:0.0143:0.4:0.03:40, wherein the alkali source was a mixture of sodium hydroxide and potassium hydroxide, and the Na / K molar ratio was 0.4. 1.90 g of aluminum sulfate 18 hydrate, 40 g of silica sol (30 wt.%), 0.14 g of NaOH, 0.48 g of KOH, 5.69 g of pyrrolidine and 116 g of deionized water were weighed respectively. The formed initial gel was transferred to a 200 ml crystallization kettle for hydrothermal treatment, and the obtained solid product was filtered and washed, and the filter cake was placed in a 100 ° C oven to dry for 12 h, and then calcined at 550 ° C for 6 h to obtain a ZSM-48 molecular sieve. According to ICP test analysis, the silicon-aluminum ratio of the obtained ZSM-48 molecular sieve was 67.

[0051] Example 3

[0052] The steps in Example 1 were repeated, except that the molar ratio of silicon source, aluminum source, pyrrolidine, alkali source and deionized water was 1:0.05:0.35:0.076:40, wherein the alkali source was a mixture of sodium hydroxide and potassium hydroxide, and the Na / K molar ratio was 0.2. 6.66 g of aluminum sulfate 18 hydrate, 40 g of silica sol (30 wt.%), 0.20 g of NaOH, 1.42 g of KOH, 4.98 g of pyrrolidine and 116 g of deionized water were weighed respectively. The formed initial gel was transferred to a 200 ml crystallization kettle for hydrothermal treatment, and then the obtained solid product was filtered and washed, and the filter cake was placed in a 100 ° C oven to dry for 12 h, and then calcined at 550 ° C for 6 h to obtain a ZSM-48 molecular sieve. According to ICP test analysis, the silicon-aluminum ratio of the obtained ZSM-48 molecular sieve was 24.

[0053] Example 4

[0054] The steps in Example 1 were repeated, except that sodium hydroxide was used as the sole alkali source. The formed initial gel was transferred to a 200 ml crystallization kettle for hydrothermal treatment, and the obtained solid product was filtered and washed, and the filter cake was placed in an oven at 100° C. to dry for 12 h, and then calcined at 550° C. for 6 h to obtain a solid powder sample.

[0055] Example 5

[0056] The steps in Example 1 were repeated, except that potassium hydroxide was used as the sole alkali source. The formed initial gel was transferred to a 200 ml crystallization kettle for hydrothermal treatment, and the obtained solid product was filtered and washed, and the filter cake was placed in an oven at 100° C. to dry for 12 h, and then calcined at 550° C. for 6 h to obtain a solid powder sample.

[0057] Example 6

[0058] The steps in Example 1 were repeated, except that the specific raw material addition order and mixing steps were not followed, but the silicon source, aluminum source, pyrrolidine, alkali source and deionized water were directly mixed uniformly to form a gel. The formed initial gel was transferred to a 200 ml crystallization kettle for hydrothermal treatment, and the obtained solid product was filtered and washed, and the filter cake was placed in an oven at 100° C. to dry for 12 hours, and then calcined at 550° C. for 6 hours to obtain a solid powder sample.

[0059] Through XRD, SEM and ICP characterization tests, it is known that the silicon-aluminum ratio of the ZSM-48 molecular sieve synthesized in Examples 1-3 ranges from 20 to 100, and its morphology is a spindle-shaped nano-needle crystal aggregation, which is a highly crystalline, low silicon-aluminum ratio product with uniform particle size distribution. It can be seen from the analysis of Examples 4-5 that when sodium hydroxide or potassium hydroxide is used as a single alkali source, the OH- provided is difficult to fully dissociate the silicon source, and it is impossible to synthesize a highly crystalline ZSM-48 product from the aluminum-rich initial gel. It can be seen from the analysis of Examples 1 and 6 that the highly crystalline low silicon-aluminum ratio ZSM-48 molecular sieve can be synthesized according to the specific material addition sequence described in the present invention. Directly mixing all the raw materials to form a gel can only obtain an amorphous silicon oxide product, which is mainly because the silicon source has not been fully dissolved and dissociated into silicon fragments by OH-, and the aluminum species cannot be effectively introduced into the skeleton. According to the method provided by the present invention, a double alkali source is used to first fully dissociate the silicon source, and then the aluminum source and the template agent are introduced to synthesize a highly crystalline low silicon-aluminum ratio ZSM-48 molecular sieve.

[0060] Comparative Example 1 (using hexamethylammonium bromide HMBr2 as template)

[0061] According to the molar ratio of SiO2, Al2O3, HMBr2, Na2O and H2O being 1:0.01:0.02:0.07:40, 0.33g sodium aluminate, 40g silica sol (30wt.%), 0.89g NaOH, 1.45g HMBr2, 116g H2O and 0.024g seed were weighed respectively to make gel hydrothermal crystallization treatment, the obtained solid product was filtered, washed, and placed in a 100℃ oven to dry for 12h, and then calcined at 550℃ for 6h to obtain a low silicon-aluminum ratio ZSM-48 molecular sieve. According to ICP test analysis, the silicon-aluminum ratio of the obtained ZSM-48 molecular sieve is 95.

[0062] Application Example 1

[0063] The ZSM-48 molecular sieves synthesized in the above Examples 1-3 and Comparative Example 1 were selected for ammonium exchange to obtain H-type ZSM-48 molecular sieve carriers, and catalysts with a Pt loading of 0.6 wt.% were prepared by impregnation method, which were respectively recorded as: Pt / Example 1, Pt / Example 2, Pt / Example 3 and Pt / Comparative Example 1. A fixed bed reactor was used to investigate the catalytic reaction performance of the catalysts for the hydroisomerization of normal hexadecane. Reaction conditions: reaction temperature 250-360°C, reaction pressure 4Mpa, mass space velocity WHSV=0.54h -1 , the hydrogen / hydrocarbon molecular volume ratio is 300.

[0064] The reaction results are as follows Figure 11-13, the catalytic performance of the catalyst prepared with the ZSM-48 molecular sieve synthesized in Examples 1-3 as the carrier is better than that of the catalyst prepared in Comparative Example 1 as the carrier. The catalytic performance of the ZSM-48 molecular sieve synthesized with pyrrolidine as the template is better than that of the ZSM-48 synthesized with hexamethylammonium bromide as the template; the catalytic activity of the sample with a silicon-aluminum ratio of 24 (Pt / Example 3) is higher than that of Pt / Example 1 (silicon-aluminum ratio of 91). In the hydroisomerization reaction of normal-hexadecane, when the conversion rate of normal-hexadecane is in the range of 20-90wt.%, the selectivity of iso-hexadecane is basically maintained at more than 90wt.%, and the overall selectivity is maintained at a high level. Table 1 lists the reaction temperature and detailed results of each catalyst when the iso-hexadecane yield is the highest. Pt / Example 3 has the highest conversion rate (95wt.%) while maintaining an iso-hexadecane selectivity of up to 97wt.%, the iso-hexadecane yield can reach 92wt.%, and the reaction temperature is relatively low (310℃). The catalyst prepared with hexamethonium bromide as the template (Pt / Comparative Example 1) has a maximum isohexadecane yield of only 79 wt.%, and the reaction temperature is 320°C.

[0065] Table 1: Results of the hydroisomerization reaction of n-hexadecane

[0066]

[0067] The above description is only a preferred specific implementation scheme of the present invention, but is not used to limit the scope of the essential technical content of the present invention. The essential technical content of the present invention is broadly defined in the scope of the claims of the application. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the claims and technical scope disclosed in the present invention, which are all within the scope of protection required by the present invention.

Claims

1. A method for synthesizing a low silicon-aluminum ratio ZSM-48 molecular sieve in a dual alkali source system, characterized in that: Here are the steps: (1) First, a mixture of an alkali source, a silicon source and deionized water is placed at 40-80° C. and vigorously stirred to obtain a mixture A; (2) mixing the aluminum source, template and deionized water uniformly, slowly adding the mixture A in step (1), and stirring thoroughly to obtain an initial gel mixture; (3) transferring the initial gel mixture into a crystallization kettle for hydrothermal crystallization at a crystallization temperature of 130-210° C. for a crystallization time of 12-72 h; either static crystallization or dynamic crystallization; (4) The solid product obtained by the hydrothermal crystallization treatment is filtered, washed, dried and calcined to obtain a ZSM-48 molecular sieve.

2. The method according to claim 1, characterized in that The template agent is pyrrolidine; The alkali source is a mixture of sodium hydroxide and potassium hydroxide; The molar ratio of silicon source, aluminum source, template, alkali source and deionized water is 1: (0.01-0.05): (0.05-1.2): (0.02-0.12): (18-50); The time for full stirring is 2-6h; The crystallization temperature is 155-195°C and the crystallization time is 24-48h; Static crystallization or dynamic crystallization with a rotation speed of 20-1000RPM.

3. The method according to claim 2, characterized in that The molar ratio of the silicon source, the aluminum source, the template, the alkali source and the deionized water is 1: (0.01-0.05): (0.2-0.8): (0.03-0.08): (25-40).

4. The method according to claim 1, characterized in that The pH range of the initial gel mixture is controlled to be 12.3-13.

8.

5. The method according to claim 1, characterized in that The stirring time in step (1) is 0.5-4h, and the stirring temperature is 40-80°C; The stirring time in step (2) is 0.1-1 h, and the stirring is carried out at room temperature.

6. The method according to claim 2, characterized in that The aluminum source is one or a mixture of two or more of aluminum nitrate, aluminum sulfate, sodium aluminate, and aluminum isopropoxide; The silicon source is one or a mixture of two or more of fumed silica, silica sol, ethyl orthosilicate and water glass; The molar ratio of the sodium hydroxide to the potassium hydroxide is Na2O:K2O=0.2-8.

0.

7. The method according to claim 2, characterized in that The low silicon-aluminum ratio ZSM-48 molecular sieve has a spindle shape formed by the aggregation of nano-needles, and its silicon-aluminum ratio ranges from 20 to 100.

8. Use of a catalyst prepared by using a metal-supported ZSM-48 molecular sieve with a low silicon-aluminum ratio obtained by the method according to any one of claims 1 to 7 in a hydroisomerization reaction.

9. The use according to claim 8, characterized in that: The metal is one of Pt, Pd, Ni and Mo or a mixture of two or more thereof.

Citation Information

Patent Citations

  • Method of synthesizing aluminum-rich molecular sieve of *MRE framework type

    CA3198683A1

  • ZSM-48 molecular sieve and preparation method and application thereof

    CN110642266A

  • ZSM-48 molecular sieve and preparation method thereof

    CN111137905A

  • ZSM-48 molecular sieve as well as synthesis method and application thereof

    CN113620309A

  • ZSM-48 molecular sieve with low silica-alumina ratio synthesized by solid-state method, hydroisomerization catalyst and application

    CN116040651A